La voix des témoins - Ana M. Alves (Carnets)
Our aim is to take a look at the telling of the story by writer-witnesses who were deported because of their Jewishness such as Primo Levi, Élie Wiesel, Jean Améry, or because of their political commitment such as Robert Antelme or Jorge Sumprun, among others, of the planned annihilation of a people. The memory of this event became an ethical and political imperative after the liberation of the camps, which is why our desire is to recall stories whose narration involves individual and collective memory.